Family spirituality and its influence on the priestly vocation of Diocesan Seminarians, Philippines - Cordova, Romelle S.; Jundos, Ruel S. (Technium Social Sciences Journal, 2023)
The study aims to identify the level of influence of parents on the priestly vocation of the diocesan seminarian among the three dioceses of Negros Occidental. It also aimed to identify significant relationship between the participants and the level of influence of family and significant difference between the level of influence of family in terms of, forming a communion of person, serving life, participating in the development of society, and sharing in the life and mission of the church. It is identified that the level of influence of family on the priestly vocation of diocesan seminarians is ‘very high’ while the influence on the role of forming a community of person is the highest. There is a significant relationship between the level of influence of family on the priestly vocation of seminarians in terms of the identified variables. However, there is no significant difference between the levels of influence of family on the priestly vocation of seminarians in terms of the identified variables. Moreover, there is no significant difference between the level of influence of family on the priestly vocation of diocesan seminarians. On the other hand, the difference was significant in the level of influence of family on the priestly vocation of seminarians in terms of serving life and sharing in the life and mission of the church when grouped according to family income. The family income of 40,001-up obtained a higher level of influence of family on the priestly vocation of seminarians in terms of serving life and sharing in the life and mission of the church than others. Though, the level of influence of parents is very high, enhancement in some aspects were viewed. Keywords: dioceses, family spirituality, seminarians, influence of parents, priestly vocation